2004
DOI: 10.1002/j.0022-0337.2004.68.10.tb03855.x
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Treatment Strategies Reported by French University Teachers

Abstract: Disparities among dental schools concerning the teaching and practice of cariology and operative dentistry can lead to variations in students' treatment modalities that can have health and economic consequences for patients and third party providers. The purpose of this study was to assess caries management strategies taught in French dental schools employing a questionnaire used in a previous study involving private dentists. The study population consisted of 180 teachers of operative dentistry. Each teacher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
5
15
0
Order By: Relevance
“…It has been suggested that practicing dentists may lack the skills to evaluate the scientific literature or that they may not know where to access information on the best current evidence in dentistry (25, 31). For whatever reason, our data are consistent with other studies that indicate there is considerable variability in clinical practice related to caries regardless of where the study was performed (32–36).…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that practicing dentists may lack the skills to evaluate the scientific literature or that they may not know where to access information on the best current evidence in dentistry (25, 31). For whatever reason, our data are consistent with other studies that indicate there is considerable variability in clinical practice related to caries regardless of where the study was performed (32–36).…”
Section: Discussionsupporting
confidence: 91%
“…For the occlusal caries lesion, the majority selected to restore when there is moderate loss of tooth substance and/or caries in the outer 1/3 of the dentin according to the radiograph. This was in agreement to what was found in Sweden [6], France [7] and Scandinavia [8]. However, they represented only 48% of the sample that was lower than the other studies.…”
Section: Discussionsupporting
confidence: 92%
“…For proximal caries lesion, the majority of responses were either restoring the tooth when the lesion reaches the enameldentin junction or progressed to the dentin outer third. Similar results were obtained from Swedish dentists [6], the French teachers [7] and the Californian dentists [1]. In our study, female dentists tend to wait until the caries lesion progressed before restoring the tooth in comparison to males.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations